Incidence, risk factors, and outcome of multidrug-resistant Acinetobacter baumannii acquisition during an outbreak in a burns unit. Issue 3 (November 2017) - Munier, A.-L.; Biard, L.; Rousseau, C.; Legrand, M.; Lafaurie, M.; Lomont, A.; Donay, J.-L.; de Beaugrenier, E.; Flicoteaux, R.; Mebazaa, A.; Mimoun, M.; Molina, J.-M.
Summary: Background: Multidrug-resistant Acinetobacter baumannii (MR-AB) can cause outbreaks in a burns unit. Aim: To study the incidence, risk factors and outcome of MR-AB colonization during an outbreak. Methods: A prospective study was conducted from April to November 2014 in a burns unit in Paris. Weekly surveillance cultures of patients and their environment were performed. MR-AB acquisition, discharge, or death without MR-AB colonization were considered as competing events. To identify risk factors for colonization, baseline characteristics and time-dependent variables were investigated in univariate and multivariate analyses using Cox models. MR-AB strains were genotypically compared using multi-locus sequence typing. Findings: Eighty-six patients were admitted in the burns unit during the study period. Among 77 patients without MR-AB colonization at admission, 25 (32%) acquired MR-AB with a cumulative incidence of 30% at 28 days (95% CI: 20–40). Median time to MR-AB acquisition was 13 days (range: 5–34). In multivariate analysis, risk factors for MR-AB acquisition were ≥2 skin graft procedures performed [hazard ratio (HR): 2.97; 95% confidence interval (CI): 1.10–8.00; P = 0.032] and antibiotic therapy during hospitalization (HR: 4.42; 95% CI: 1.19–16.4; P = 0.026). A major sequence type of MR-AB (ST2) was found in 94% and 92% of patients and environmental strains, respectively, with all strains harbouring the blaOXA-23 gene. MR-AB colonization increased length of hospitalization (HR: 0.32; 95% CI: 0.17–0.58; P  = 0.0002) by a median of 12 days. Conclusion: A high incidence of MR-AB acquisition was seen during this outbreak with most strains from patients and their environment belonging to single sequence type. MR-AB colonization was associated with more skin graft procedures, antibiotic use, and prolonged hospitalization.